Enhancing Socio-Economic Sustainability in South Africa: A Review of Local Municipalities in Managing Inward Migration from the Periphery to the Core - Maenetja, Refilwe Erna; Kgobe, France Khutso Lavhelani (Universitas Medan Area, 2024)
This conceptual paper aims to examine the prevailing patterns of migration from local municipalities to metropolitan areas in the context of socio-economic transformations. Emphasizing the crucial role of local municipalities in addressing and mitigating migration towards urban cores, the paper underscores that the effectiveness of such efforts relies on factors like good governance, enhanced economic prospects, basic service provision, infrastructure development, and tailored skills training within the unique context of each municipality. Migration is a multifaceted phenomenon entwining economic, socio-cultural, and security dimensions. The unsustainable influx from the periphery burdens metropolitans, particularly in rural regions, challenging the mandated responsibilities. The failure of local municipalities to adequately deliver services exacerbates the strain on metropolitans already grappling with limited resources. The migration exodus from rural to urban centers often stems from pervasive socio-economic disparities, making migration a perceived solution to enhance the quality of life. Despite the advent of democracy, developmental progress in rural areas remains limited, necessitating a comprehensive approach that integrates rural development strategies with urban planning, job creation in urban areas, and the resolution of systemic issues. It is crucial to acknowledge that addressing migration requires a holistic perspective, as rural development alone may not suffice to deter migration to urban centers, given the diverse opportunities and amenities they offer. The paper advocates for a coordinated, multi-stakeholder approach involving governmental bodies, local communities, NGOs, and the private sector to achieve meaningful and sustainable results in curbing migration from local municipalities to metropolitan areas. In conclusion, the study underscores the importance of achieving a more balanced and sustainable population distribution across municipalities for overall societal well-being.